El desarrollo del arte durante y luego de la última mitad de la pandemia del COVID-19 - Mite Laurido, Francisco Alfredo (2023)
Cultural diffusion is of great importance within a context of crisis, since art is a historical guarantor of a society, and an educational medium through its dissemination in broad communication media such as social networks, where users can consume it in anytime, anywhere. This academic work unfolds the course of the art process and its dissemination in different cycles, places, together with populations, giving relevance to problems similar to the COVID-19 pandemic that stopped the cultural passage due to mass confinement as a regulatory protection measure. The diffusive impulse of the pictorial artist during the pandemic is exposed, treating his difficulties such as the lack of capacity in the city, where it is denoted that the live public is the largest consumer of his works; Thus, several alternatives are postulated in the artist's mind to educate the masses, without human contact being a determining problem. The chosen sector was the neighborhood of Las Peñas, located in the Tarqui parish (Guayaquil - Ecuador), of three artistic painters, it is sustained how the diffusive result was when projecting their paintings on Facebook and Instagram, social networks that prioritize images for the digital interaction; the strategies of the publications are evaluated, together with the impact on the audience.